The Effects of Students' Perception on Teacher’s Pedagogic Competence and Language Attitude Towards Student’s English Achievement - Nupus, Hayati (Journal of English Education Studies, 2019)
This research is a kind of survey and aims to find and analyze empirically the efects of student perception on Teacher’s pedagogic competence towards student’s English achievement, the effects of language attitude towards Student’s English achievement, and the effects of The student perception on teacher’s pedagogic competence and language attitude towards student’s English achievement. The Method used in this research is a survey method. The observed population of this research is student of second grade of state vocational high schools in Serang-Banten, sample was taken as many as 50 students, the sample was gained through simple random sampling, which means that the reseacher mixed the subjects in the population so that they will be considerably the same. The collecting of the data used by the questioner and collecting of student’s English achievement. The gained data was analyzed by using correlation technique and multiple regressions. Previously, the prerequisite test before examining the regression test must be accomplished, such as normality test and linearity test. This research is done on October 2017. The result of the research concluded: 1).There are any significant effects of student perception on Teacher’s pedagogic competence and Language Attitude collaboratively towards students’ English Achievement students at State Vocational High Schools in Serang-Banten. It can be proved by Sig = 0,000 < 0.05 and Fo = 47,843, 2).There is a significant effect of student perception on Teacher’s pedagogic competence towards students’ English Achievement students at State Vocational High Schools in Serang-Banten. It can be proved by Sig = 0,010 < 0.05 and th = 2,677, 3).There is a significant effect of the Language Attitude towards students’ English Achievement students at State Vocational High Schools in Serang-Banten. It can be proved by Sig = 0.000 < 0.05 and th = 4,137.